Faktor – Faktor yang Berhubungan dengan Kepatuhan Berobat Pasien Glaukoma di Kota Padang - Dwi Christina Rahayuningrum; Ratna Indah Sari Dewi; Nurmayanti Nurmayanti (Malahayati Nursing Journal, 2022)
ABSTRACT  WHO an estimated 39 million people in the world suffer from blindness and glaucoma accounted for 4.5 million or approximately 12%. Patient noncompliance in glaucoma can be influenced by the attitude and family support. The purpose of this study to determine the factors - factors related to treatment compliance in patients with glaucoma in UPTD BKIM West Sumatra. Cross sectional study design. The research was conducted in September 2019, population of 284 people and a sample of 74 patients who visit UPTD BKIM West Sumatra. Sampling with accidental sampling technique by using research instrument in the form of a questionnaire. The results showed more than half (56.8%) of respondents did not obey treatment, more than half (55.4%) of respondents had low knowledge, more than half (52, 7%) of the respondents have the negative attitude, and more than half (54.1%) support poor families. Chi-Square test results obtained knowledge with treatment compliance (p-value 0.000), attitude and treatment compliance (p-value 0.000), and family support with treatment compliance (p-value 0.000). It was concluded that there is a correlation between knowledge, attitude and family support adherence in patients with glaucoma in UPTD BKIM West Sumatra. It is suggested to the leadership of health professionals continue to improve the screening and counseling about the factors - factors that affect treatment compliance, especially glaucoma patients, and family support with treatment compliance (p-value 0.000). Keyword: Compliance, Knowledge, Attitude and Family Support, Blindness  ABSTRAK Data WHO memperkirakan 39 juta orang didunia menderita kebutaan dan glaukoma menyumbang sebesar 4,5 juta atau sekitar 12%. Ketidakpatuhan Pasien glaukoma dalam dapat dipengaruhi oleh sikap dan dukungan keluarga. Tujuan penelitian ini untuk mengetahui faktor – faktor yang berhubungan dengan kepatuhan berobat pada pasien glaukoma di UPTD BKIM Sumatera Barat. Desain penelitian cross sectional study. Penelitian dilaksanakan pada bulan September 2019, dengan jumlah populasi 284 orang dan sampel 74 orang pasien yang berkunjung ke UPTD BKIM Sumatera Barat. Pengambilan sampel dengan teknik accidental sampling dengan menggunakan instrument penelitian berupa kuesioner. Hasil penelitian didapatkan lebih dari separuh (56,8%) responden tidak patuh berobat, lebih dari separuh (55,4%) responden memiliki pengetahuan rendah, lebih dari separuh (52,7%) responden memilki sikap negatif, dan lebih dari separuh (54,1%) dukungan keluarga yang kurang baik. Hasil uji Chi-Square didapatkan pengetahuan dengan kepatuhan berobat (p-value 0,000), sikap dengan kepatuhan berobat (p-value 0,000), dan dukungan keluarga dengan kepatuhan berobat (p-value 0,000). Disimpulkan bahwa terdapat hubungan pengetahuan, sikap, dan dukungan keluarga dengan kepatuhan pada pasien Glaukoma di UPTD BKIM Sumatera Barat . Disarankan kepada pimpinan tenaga kesehatan terus meningkatkan skrining dan penyuluhan tentang faktor – faktor yang mempengaruhi kepatuhan berobat khususnya pasien glaukoma. Kata Kunci: Kepatuhan, Pengetahuan, Sikap dan Dukungan Keluarga, Kebutaan